Journeys through our contemporary world - San Juan, David Michael M. (Quezon City : Vibal Group, Inc., 2018)
"This book was written as a complete resource material for teachers and students of the subject The Contemporary World. The analytical texts in the book were written in a fairly balanced manner, highlighting the major arguments of both sides in every globalization-themed debate. This book essentially tackled globalization's many facets and the problems related with it, while at the same time providing alternative solutions that will help bring to birth a better world for everyone."
Includes bibliography and index.
English text.
Keywords: Globalization